The effects of sociocultural factors on creativity implications for teaching disadvantaged pupils at Tahanan Special School-Hiyas - Orola, Elizabeth N.,#eauthor.; Adorio, Mercedes P. (Quezon City College of Education, University of the Philippines Diliman, 1975)
The purpose of the study is to determine the effects of socio-cultural factors (sex and socio-economic status) on the creative behavior of 39 children on the Torrance Tests of Creative Thinking, Figura; Form B. The hypothesis of the study is that there is no relationship between the sociocultural status of a pupil and his creative behavior. The findings of the study reject the null hypothesis. An inference is made based on the findings of the study, that delinquent subjects scored lower than their non delinquent counterparts in the nonverbal tests of creative thinking.
Thesis (Master of Arts in Teaching Special Education - Behavioral Problems)--University of the Philippines, Diliman
Keywords: Creative ability -- Philippines -- Manila; Special education -- Philippines -- Manila